Assessment of Sea Turtle Welfare Using an Animal Welfare Approach at Nipah Beach Hatchery - Nadira Khairunnisa; Maiser Syaputra; Fauzan Fahrussiam (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The decline in sea turtle populations highlights the importance of conservation efforts through captive management that prioritizes animal welfare. This study aimed to assess the level of sea turtle welfare at the Turtle Conservation Community (TCC) hatchery in Nipah Beach, North Lombok Regency. The research was conducted in June 2025 using field observation, in-depth interviews, and a scoring method based on the five animal welfare principles referring to the Regulation of the Director General of PHKA No. P.6/IV-SET/2011. The results showed that the overall welfare score of sea turtles was 73.21, classified as good. Feeding management and health aspects received high scores, while the natural behavior aspect showed the lowest score. Improvements are needed, particularly in enclosure enrichment, environmental security, and feed variation, to further optimize sea turtle welfare.